(untitled) (The International Journal for Scientific Research, 2023)
Introduction: The availability of prescription drugs as OTC medications is also becoming more common. However, self-medication carries risks such as misdiagnosis, use of excessive drug doses, prolonged use, and drug interactions. This review aimed to collect evidence about the impact of self-medications on health outcomes. Methods: The systematic review in this study involved several steps to identify and assess relevant research. The search phase involved finding potentially relevant studies in various databases such as PubMed, PsychInfo, EBSCO Medline, BioMed central, and Science Direct. The screening phase involved applying predetermined inclusion and exclusion criteria to determine which studies were appropriate for the review. To conclude the selection process, the full text of the articles was reviewed to determine whether they met the inclusion criteria. Additionally, the full text of review articles was reviewed to identify any additional articles that might be relevant and included in the review. Results: A total of 17 studies were found that met the inclusion criteria. The majority (11/17) of these studies were cross-sectional and relied on self-report. The combined sample size of the 17 studies was 28,628 (ranging from 5 to 5,426), and the average response rate was 66%. In 76% of the studies, reported self-treatment was 50% (ranging from 12% to 99%). Overall, only one or two respondents were registered with a general practitioner (GP) or primary care physician (mean of 56%, ranging from 21% to 96%). In the 13 studies that provided information on self-prescription, the mean percentage of physicians reporting self-prescription was 61% with a standard deviation of 25% and a range of 9% to 99%. Conclusions: Although many patients view over-the-counter (OTC) medications as completely safe, their use always carries some degree of risk for the consumer. This is especially true for patients who do not follow the instructions on the label or package insert.